Do generalists and specialists agree on descriptive acne morphology?. (19th September 2011) - Yazdanyar, S.; Bryld, L.E.; Heidenheim, M.; Jemec, G.B.E.
Abstract Background Acne is a common skin disease, which is treated by many different specialities. Clinical guidelines for treatment are based on the recognition of acne morphology. The assessment of acne morphology is therefore an important element of the proper diagnosis and treatment of acne. Objective To evaluate the level of congruence in the assessment of acne morphology in General Practitioners (GPs) and Dermatologists compared to the assessment of an expert. Methods The study was conducted during 2008–2009. Randomly selected GP and Dermatologists Practitioners, (DPs) from Denmark were invited to complete an on‐line questionnaire. The questionnaire was based on seven cases, each presented with digital photos and a short history. The respondents were asked to identify the morphology by marking their answer on a closed list. Congruence, variation and the participants' assessment were compared with a priori expert assessment using odds ratios, Fishers exact test and Index of Qualitative Variation. Results Of the 1700 GPs and 110 DPs invited, 355 GPs and 99 DPs participated. In all seven cases, DPs were more in accordance with expert opinion than were GPs. In addition, the GPs had a greater variation in the distribution of answers. Conclusion GPs described acne morphology recognized clinical hallmarks of severity in acne less well than dermatologists and were far less consistent.